THE CHANGING ROLE OF COLORS IN INDIAN PAINTING (A BRIEF STUDY): भारतीय चित्रकला में रंगों की परिवर्तनशील भूमिका (एक संक्षिप्त अध्ययन) - Maurya, Anjana (International Journal of Research -GRANTHAALAYAH, 2014)
In painting, the artist expresses his expressions through lines and colors. Rango's attachment to ancient cave dwellers from glass windows to peeping humans has never diminished. Rather, he has moved forward, playing the conditions of the country. Our Indian art line has been predominant. But colors have also contributed their full beauty to their beauty. Because the coordination of colors with the line only creates one panoramic pictures in Ajanta and the whole world talks about its beauty. The line and color complement each other. Lines are obtained only by aesthetic colors. The artists, while interacting with Rango, do not know how many asynchronous creation takes place. If not color or not an artist. Therefore we can say that not only the artist but the world also needs colors. Because if the color ends from our life, then all the beauty ends, therefore colors have a very important contribution in our life. Which we are going to discuss further. चित्रकला में कलाकार अपने भावों की अभिव्यक्ति रेखा तथा रंगों के माध्यम से करता है। प्राचीन गुहावासियों से लेकर काँच की खिड़कियों से झाँकने वाले मानव तक रंगो का लगाव कभी कम नहीं हुआ है। बल्कि देशकाल की परिस्थितियों को निभाते हुए वह आगे बढ़ा है। हमारी भारतीय कला रेखा प्रधान रही है। परन्तु रंगों ने भी उनके सौन्दर्य में चार चाँद लगाने में अपना पूर्ण योगदान दिया है। क्योंकि रेखा के साथ रंगों का समन्वय होने पर ही अजन्ता में एक से एक नयनाभिराम चित्रों का सृजन हो पाया और उसके सौन्दर्य की चर्चा सारा विश्व करता है। रेखा और रंग एक दूसरे के पूरक है। रेखाओं को सौन्दर्य रंगो द्वारा ही प्राप्त होता है। कलाकारों ने रंगो के साथ अठकेलीया करते हुए न जाने कितने अस्वर्णिम सृजन कर डालता है। अगर रंग नही ंतो कलाकार नहीं। इसलिए हम कह सकते है कि कलाकार को ही नही बल्कि विश्व को भी रंगों की आवश्यकता है। क्यांेकि अगर हमारे जीवन से रंग खत्म तो सारी खूबसूरती खत्म इसलिए रंगों का हमारे जीवन में बहुत ही महत्वपूर्ण योगदान है। जिसकी हम आगे विवेचना करने जा रहे है।